Arguing under the Qiqayon: An Introduction to a Set of Articles on Jonah - Philippe Guillaume (Journal of Hebrew Scriptures, 2009)
As per title, an introduction to the following six articles that deal with the Book of Jonah. All but the final essay in the series reflect issues hotly debated at the conference of the European Association of Biblical Studies at Lisbon in August 2008. The final essay (article 9 in this volume of JHS) is based on a paper presented at the Society of Biblical Literature conference at Boston in November 2008.